(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
This article presents a reflection on the methodology used to teach sewing techniques in Fashion Design Courses. Sewing techniques have been transmitted for generations informally, and lack academic systematization. In Brazil, the transmission of knowledge since the end of the 19th century has occurred in professional courses. With the creation of fashion design courses in the 1980s, the teaching of sewing techniques became part of the academic scope. Mastering sewing techniques can interfere with and enrich the fashion professional’s creative process. The systematization of procedures and the creation of a methodology to be followed within the academic sphere is presented in this article, in order to be replicated in other courses as well as demonstrating its potential.